Peran Kepala Madrasah Dalam Meningkatkan Profesionalitas Guru Di MTS Negeri 2 Medan - Arya Winanda; Amiruddin Siahaan; Inom Nasution (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The role of the madrasa head as supervisor has been to try to support teacher professionalism through planning supervision programs, implementing and following up on the results of supervision evaluations, but up to now there are still teachers who do not understand the tasks that must be fulfilled by a teacher. This research aims (1) to determine the role of the madrasa head in improving the professionalism of teachers at MTSN 2 Medan, (2) to determine the implementation of the role of the madrasa head in improving the professionalism of teachers at MTSN 2 Medan. This research uses a qualitative approach with the case study method. There were 3 informants in this research, namely the Head of Madrasah, Deputy Head of Madrasah I, Head of Administration and also Teachers. Data collection techniques use observation, interviews and documentation. Data validity techniques use triangulation. The research results in this study are the role of the Madrasah Head at MTsN 2, through a clear vision, inclusive approach, comprehensive professional development program, use of data in decision making, and prioritization of student welfare, has succeeded in creating a school environment that is conducive to improving quality. education and teacher professionalism. The innovations carried out by the Madrasa Head at MTsN 2 have succeeded in improving the professionalism of teachers and staff, as well as the overall quality of education.